Review about Luis Íñigo Fernández: Brief History of Spain I. The roots. Brief History of Spain II. The way of modernity - Editorial, Equipo (Avances en Supervisión Educativa, 2011)
TÍTULO: BREVE HISTORIA DE ESPAÑA, I. LAS RAÍCES.EDITORIAL: NOWTILUSISBN: 9788497639187TÍTULO: BREVE HISTORIA DE ESPAÑA, II. EL CAMINO DE LA MODERNIDAD.EDITORIAL: NOWTILUSISBN: 9788497639217